2021
DOI: 10.3390/ijms22168715
|View full text |Cite
|
Sign up to set email alerts
|

Regular Physical Exercise Modulates Iron Homeostasis in the 5xFAD Mouse Model of Alzheimer’s Disease

Abstract: Dysregulation of brain iron metabolism is one of the pathological features of aging and Alzheimer’s disease (AD), a neurodegenerative disease characterized by progressive memory loss and cognitive impairment. While physical inactivity is one of the risk factors for AD and regular exercise improves cognitive function and reduces pathology associated with AD, the underlying mechanisms remain unclear. The purpose of the study is to explore the effect of regular physical exercise on modulation of iron homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…We found that cognitive performance was influenced by physical inactivity (“Delayed memory” domain) and hypertension status (“Attention” domain and total cognition score). The beneficial influence of physical activity on cognition might be due to increased cerebral blood flow positively affecting neuronal plasticity and memory ( Belaya et al, 2021 ). It has been suggested that both cognitive and physical exercise training may be useful to influence age-related cognitive abilities ( Jardim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that cognitive performance was influenced by physical inactivity (“Delayed memory” domain) and hypertension status (“Attention” domain and total cognition score). The beneficial influence of physical activity on cognition might be due to increased cerebral blood flow positively affecting neuronal plasticity and memory ( Belaya et al, 2021 ). It has been suggested that both cognitive and physical exercise training may be useful to influence age-related cognitive abilities ( Jardim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in an in vivo study, IL-6 overexpression induced the reduction in neuroinflammation at the Aβ level rather than aggravating the pathology of Aβ plaques [ 73 ]. Irina Belaya et al reported regular exercise can modulate iron homeostasis in WT mice and in a mouse model of AD via the IL-6/STAT3/JAK1 pathway [ 74 ], indicating that M2 type microglia are mainly activated, which enhances the phagocytic function of Aβ [ 73 ]. The combination of IL-18 and its receptor complex can activate c-Jun N-terminal kinase (JNK) and MAPK-p38, thereby activating endogenous and exogenous pro-apoptotic signaling pathways [ 75 ].…”
Section: Il-37 In Cns Diseasesmentioning
confidence: 99%
“…Iron-dysregulation homeostasis is well-known and evident in AD [2], but there is still little known about the influence of physical exercise on iron metabolism in the brain and peripheral nervous system, as well as the mechanisms responsible for exercise-induced iron regulation in AD. In the animal model, long-term voluntary running induced the redistribution of iron, which had an impact in altered iron metabolism and trafficking in the brain, and increased iron content in skeletal muscle [46]. Belaya et al found that exercise reduced levels of cortical hepcidin, a key regulator of iron homeostasis, and reduced the levels of interleukin-6 (IL-6) in cortex and plasma [46].…”
Section: Introductionmentioning
confidence: 99%
“…In the animal model, long-term voluntary running induced the redistribution of iron, which had an impact in altered iron metabolism and trafficking in the brain, and increased iron content in skeletal muscle [46]. Belaya et al found that exercise reduced levels of cortical hepcidin, a key regulator of iron homeostasis, and reduced the levels of interleukin-6 (IL-6) in cortex and plasma [46]. The authors stated that regular exercise can induce a reduction in hepcidin in the brain, possibly via the IL-6/STAT3/JAK1 pathway [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation